(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Retinopathy of prematurity is considered as an important cause of blindness. This prospective study was undertaken to document the frequency and the associated factors of retinopathy of prematurity among 97 preterm newborn weighing <2000 g and/or with a gestation of <35 weeks. The first eye examination was performed by an ophthalmologist at 4 weeks of postnatal age for the infants born at ?30 weeks of gestation or birth weight ?1200 g and at 3 weeks of postnatal age for the infants <30 weeks of gestation or birth weight <1200 g. The overall incidence of retinopathy of prematurity was 23.7%. Premature newborn with retinopathy was having significant low mean birth weight (p=0.001) and the mean gestational age (p=<0.001) when compared with newborns without retinopathy of prematurity. Newborns with retinopathy of prematurity were requiring a longer duration of oxygen (p=0.005) than that of non-retinopathy of prematurity newborns. Logistic regression shows the duration of oxygen in the hospital and lower gestational age were independent risk factors of retinopathy of prematurity. Prematurity and longer duration of oxygen administration were the risk factors for the development of retinopathy of prematurity.